Delayed neutrophil apoptosis enhances NET formation in cystic fibrosis. Issue 2 (15th September 2017) - Gray, Robert D; Hardisty, Gareth; Regan, Kate H; Smith, Maeve; Robb, Calum T; Duffin, Rodger; Mackellar, Annie; Felton, Jennifer M; Paemka, Lily; McCullagh, Brian N; Lucas, Christopher D; Dorward, David A; et al.
Abstract : Background: Cystic fibrosis (CF) lung disease is defined by large numbers of neutrophils and associated damaging products in the airway. Delayed neutrophil apoptosis is described in CF although it is unclear whether this is a primary neutrophil defect or a response to chronic inflammation. Increased levels of neutrophil extracellular traps (NETs) have been measured in CF and we aimed to investigate the causal relationship between these phenomena and their potential to serve as a driver of inflammation. We hypothesised that the delay in apoptosis in CF is a primary defect and preferentially allows CF neutrophils to form NETs, contributing to inflammation. Methods: Blood neutrophils were isolated from patients with CF, CF pigs and appropriate controls. Neutrophils were also obtained from patients with CF before and after commencing ivacaftor. Apoptosis was assessed by morphology and flow cytometry. NET formation was determined by fluorescent microscopy and DNA release assays. NET interaction with macrophages was examined by measuring cytokine generation with ELISA and qRT-PCR. Results: CF neutrophils live longer due to decreased apoptosis. This was observed in both cystic fibrosis transmembrane conductance regulator (CFTR) null piglets and patients with CF, and furthermore was reversed by ivacaftor (CFTR potentiator) in patients with gating (G551D) mutations. CF neutrophils formed more NETs and this was reversed by cyclin-dependent kinase inhibitor exposure. NETs provided a proinflammatory stimulus to macrophages, which was enhanced in CF. Conclusions: CF neutrophils have a prosurvival phenotype that is associated with an absence of CFTR function and allows increased NET production, which can in turn induce inflammation. Augmenting neutrophil apoptosis in CF may allow more appropriate neutrophil disposal, decreasing NET formation and thus inflammation.